Definition of the coronatus species-group (Hymenoptera: Bethylidae, Dissomphalus) with description of thirteen new species - Alencar, I. D.c.c.; Azevedo, C. O. (Zootaxa, 2006)
The following thirteen new species of Dissomphalus from the Neotropical region are described and illustrated: D. aculeatus, D. auritus, D. coronatus, D. culteratus, D. declinatus, D. decussatus, D. flexuosus, D. galeatus, D. hirtus, D. pronus, D. ramosus, D. sinatus, and D. uber. The coronatus group is suggested to accommodate them, which is defined by having mandible tridentate, sublateral tergal process with a pair of depressions, each with dense tuft of setae directed backward, antero-lateral margin of depression setose, tubercle absent, genitalia with inner apical surface of paramere generally with one seta distinctly longer than the others, ventral ramus shorter than dorsal body with at least a part inclined and tending to be convergent mesad and aedeagus with dorsal body wide with a crown-like structure. A key to the thirteen new species and a discussion of similar species are included.